Pengambilan Keputusan Strategi Dalam Pencapaian Target Migrasi Pelanggan Prabayar Pada PLN UP3 Tanjung Karang - Lestira Putri Warganegara, Tri; Septiadi, Sendi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
Prepaid electricity or smart electricity is a service for using electrical energy by means of pln customers paying the initial fee to obtain electrical energy for use or using a token system, so that customers do not need to deal with the monthly electricity bill payment schedule and can make it easier for customers to control electricity usage and Prepaid electricity is also expected to be able to reduce late payments or what can be called arrears. The aim of the researchers in this study is to analyze and find out what strategies are appropriate in an effort to achieve the migration target of prepaid electricity customers at PT PLN (Persero) UP3 Tanjung Karang using the AHP (Analytical Hierarchy Process) method and Expert Choice analysis tools that are useful for giving weights. with the aim of obtaining priority strategies. The conclusion of this study shows the right strategy to achieve the prepaid customer migration target in this research, namely improving prepaid customer service followed by free UJL promos and discounts on adding power to pln mobile and village migration programs.